Optimizing Inventory for Chicken Egg Livestock Industry - Cherish Rikardo; Alfian Tan; Paulina Kus Ariningsih (Universitas Katolik Parahyangan, 2019)
This study is to give an alternative of an optimum inventory model for chicken egg livestock industry. The characteristic of the egg livestock industry is very unique; since the chicken breeding performance varies. In a particular span of time, the industry might have ameliorating and deteriorating characteristics. Some farmers nourish several generations at the same time. This study generates a mathematical model to optimize the length time between purchases of a chicken generation to get optimum cost by considering demand seasonality. This study is also generating the algorithm to find the optimum solution in a simple way. Future potential researches are also stated.Keywords: Optimization, inventory, egg, chicken, ameliorating